Rukun Iman & Rukun Islam courseware based on ADDIE Model (RIRI) / Mohd Fethri Nordin - Nordin, Mohd Fethri (2014)
Nowadays, the usage of multimedia courseware has been widely used for educational purposes. This courseware is developed for help the teacher’s more easily teach their students in interactive learning method. Besides that, this courseware can help the students more understand the content provide to them because it provide element of graphical, text, audio, video and also animation. ADDIE model was chosen as a instructional model for this project. So, this courseware has been developed to enhance the existing application and teach them more using interactive method. RIRI courseware was designed and develops using tools that can easier the user open it in short time because all file are combine into portable executable file that has small size of file. The questionnaire has been distributed to the target user to get the feedback about the project. As a results, all of the target user are strangle agree and agree that this courseware are meet their satisfaction. Some future enhancements are needed during the process testing the courseware. Developer needs to aware the compatibality of each of the desktop that user use before installed the file to them.